Assessment of Supply Chain Agility in the Indian Garment Industry - Rai, Siddharth Shankar; Giri, Sunil (Asian Journal of Empirical Research, 2019)
The research aims to provide a supply chain agility framework with stage-wise holistic assessment of the performance and binding relationships. The study considers agility at three stages: supply, manufacturing, and distribution. It applies structural equation modelling to examine the impact of major determinants as strategic partnership, information sharing, resilience, sourcing flexibility, and order fulfillment flexibility on stage-wise agility in the supply chain. The analysis has uncovered that manufacturing agility is affected by all the determinants while supply agility is not affected by any constructs of flexibility of sourcing and order fulfillment in the Indian garment industry. Distribution agility is significantly affected by all the determinants but information sharing and resilience, which can be caused by infrastructure constraints in the Indian conditions. The research provides important implications for practitioners and researchers.